Political Fragmentation of the Mongol Empire: Islam, Diplomacy, and Power Rivalries in the Middle East1260-1266 AD - Anggi Supriyadi; Idris Ahmad Rifai (CV. FOUNDAE, 2025)
This article discusses how the rivalry between Berke and Hulagu Khan in 1260-1266 reflects the complex dynamics of power, religion and diplomacy in the Mongol Empire. Berke Khan, the Muslim leader of the Golden Horde, challenged Hulagu Khan's superiority over the Ilkhan supported by Mongu Khan in Karakuram. The rivalry between the two not only became a battle between Mongol factions, but also marked a major geopolitical shift with Islam as one of the unifying elements within Islamic Mongol rule. Through clever diplomacy, Berke Khan forged a strategic alliance with the Egyptian Mamluks to restain Hulagu's military expeditions into Egypt, especially in the context of the threat to Islamic civilization after the destruction of Baghdad. This study explores how religious identity, diplomatic strategy and political power interacted to shape the historical landscape. It analyzes the long-term impact of the conflict on the stability of the Central Asian region, the Middle East, and the political transformation of the Mongol Empire. Using a historical and geopolitical approach, the study argues that Berke's rivalry with Hulagu Khan became an important episode in history to protect Islamic civilization from attempts at total destruction by the Mongols.